Synergistic Phase and Disorder Engineering in 1T‐MoSe2 Nanosheets for Enhanced Hydrogen‐Evolution Reaction. Issue 28 (19th May 2017) - Yin, Ying; Zhang, Yumin; Gao, Tangling; Yao, Tai; Zhang, Xinghong; Han, Jiecai; Wang, Xianjie; Zhang, Zhihua; Xu, Ping; Zhang, Peng; Cao, Xingzhong; Song, Bo; et al.
Abstract : MoSe2 is a promising earth‐abundant electrocatalyst for the hydrogen‐evolution reaction (HER), even though it has received much less attention among the layered dichalcogenide (MX2 ) materials than MoS2 so far. Here, a novel hydrothermal‐synthesis strategy is presented to achieve simultaneous and synergistic modulation of crystal phase and disorder in partially crystallized 1T‐MoSe2 nanosheets to dramatically enhance their HER catalytic activity. Careful structural characterization and defect characterization using positron annihilation lifetime spectroscopy correlated with electrochemical measurements show that the formation of the 1T phase under a large excess of the NaBH4 reductant during synthesis can effectively improve the intrinsic activity and conductivity, and the disordered structure from a lower reaction temperature can provide abundant unsaturated defects as active sites. Such synergistic effects lead to superior HER catalytic activity with an overpotential of 152 mV versus reversible hydrogen electrode (RHE) for the electrocatalytic current density of j = −10 mA cm −2, and a Tafel slope of 52 mV dec −1 . This work paves a new pathway for improving the catalytic activity of MoSe2 and generally MX2 ‐based electrocatalysts via a synergistic modulation strategy. Abstract : Synergistic regulation of crystal phase and disorder engineering in partially crystallized 1T phase MoSe2 nanosheets that are directly hydrothermally synthesized enhances catalytic activity toward the hydrogen‐evolution reaction (HER). The optimized MoSe2 nanosheets exhibit a record‐high HER catalytic activity, with η = 152 mV versus RHE for j = −10 mA cm −2 and a Tafel slope of 52 mV dec −1 .